Enhancing the Employment Chances of Roma - Bodewig, Christian; Kureková, Lucia (World Bank, Washington, DC, 2012)
Roma communities in central and southeastern Europe have a history of being excluded from the labor market and still face severe barriers to employment. Besides being marginalized socially, Roma were typically the first to lose their jobs at the outset of the post-communist transition. Many in their next generation grew up in unemployed households, with low educational attainments and limited job skills. The labor market exclusion of Roma persisted even through the years of buoyant economic growth and increasing employment levels prior to the economic slowdown triggered by the global financial crisis in 2008. Many governments in central and southeastern Europe are trying to address the unemployment problem of Roma and other disadvantaged groups by introducing measures to restrict or cut welfare benefit entitlements, so as to strengthen incentives to work. However, research by the World Bank and others shows that simply cutting benefits is unlikely to result in higher employment the labor market exclusion and social marginalization of Roma is a multifaceted issue, and their communities face multidimensional barriers to employment. A more effective way to promote employment among Roma (and other disadvantaged groups) is the employment activation approach increasingly being introduced across many countries in the European Union and the Organization for Economic Co-operation and Development (OECD). This approach balances the mutual obligations of jobseekers and state employment offices in order to secure the successful integration of the most disadvantaged workers.